The influence of middle-aged and older adults’ social capital and education on physical function: evidence from the China Health and Retirement Longitudinal Study - Man, Tingfai; Zhao, Yongze; Mai, Huaxin; Bian, Ying (Frontiers in Public Health, 2024)
BackgroundPopulation aging is a major global trend with significant social, economic, and health implications. In China, the increasing aging population presents challenges, including increased chronic diseases and disabilities. Social capital has emerged as vital in determining health outcomes for middle-aged and older adults. This study seeks to examine the impact of social capital and educational attainment on physical functioning in middle-aged and older adults, with particular emphasis on the moderating effect of education within this relationship.MethodsThis study utilized data from the China Health and Retirement Longitudinal Study (CHARLS) from 2018 to 2020, involving 9,497 participants aged 45 and older. Physical function was assessed using the Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) scales. Social capital was measured in four dimensions: social trust, social support, social participation, and reciprocity. Educational attainment was categorized into four levels: below primary school, primary school, middle school, and high school or above. Cox proportional hazards regression and moderating effect models were used for data analysis, adjusting for demographic and health-related variables.ResultsOur findings highlight the significant roles of social participation (aHR = 0.856, 95%CI: 0.675–0.809) and reciprocity (aHR = 0.700, 95%CI: 0.626–0.784) in improving physical function. Education enhanced the positive effects of social participation (aHR = 0.923, 95%CI: 0.840–0.980). Subgroup analyses showed that social support was a protective factor for females (aHR = 0.857, 95% CI: 0.737–0.998), while social trust negatively affected urban residents (aHR = 1.330, 95%CI: 1.135–1.560).ConclusionThe findings underscore the importance of social participation, reciprocity, and education in enhancing physical function among middle-aged and older adults. Tailored interventions addressing gender and residential differences are essential to meet the unique needs of various subgroups. Understanding the relationship between social capital, education, and health can inform strategies to improve this population’s well-being.